Impact of fluoride and aluminum co-exposure on bone growth and quality in juvenile rats: dose and duration effects - Shi-Ying Luo; Hong-Ying Liang; Mei-Gui You; Wen Chen; Zhi-Guo Zhong; Yan Chen (Ecotoxicology and Environmental Safety, 2024)
This study aimed to investigate the impact of the dosage and duration of fluoride and aluminum(F and Al) co-exposure on the skeletal growth and bone quality of juvenile rats. Forty-eight 8-week-old Sprague-Dawley rats were randomly assigned to normal control, low F and Al exposure, and high F and Al exposure groups, with 45-day and 90-day subgroups established for each. We measured body length, tibia length, conducted bone histomorphometric analysis of the proximal tibia, performed micro-CT scans and three-point bending tests of the femur. Compared to the age-matched control group, the low F and Al group at 45 days exhibited increased bone formation and stiffness; the low F and Al group at 90 days and the high F and Al group at 45 days showed increases in body length, tibia length, growth plate width, longitudinal bone growth rate, bone turnover, and improved microstructure. Notably, bone elastic stress only elevated in the high F and Al group at 45 days. Conversely, the high F and Al exposure group at 90 days experienced decreases in the aforementioned parameters, with the exception of growth plate width, and displayed abnormal hypertrophic chondrocyte morphology in the growth plate. In summary, long-term exposure to low levels of F and Al and short-term exposure to high levels of F and Al promote bone formation followed by bone resorption in juvenile rats, stimulating bone growth and enhancing bone quality. However, long-term exposure to high levels F and Al results in low bone turnover, slow bone growth, and reduced bone property.